2002
DOI: 10.1038/sj.leu.2402598
|View full text |Cite
|
Sign up to set email alerts
|

F-MuLV acceleration of myelomonocytic tumorigenesis in SV40 large T antigen transgenic mice is accompanied by retroviral insertion at Fli1 and a novel locus, Fim4

Abstract: We describe here the development of a murine system for the identification of genes involved in myelomonocytic neoplasms. Transgenic C57BL/6J mice expressing SV40 early region under a myelomonocytic promoter develop histiocytic sarcomas with a latency of 167 days. We used retroviral proviral tagging to accelerate tumorigenesis and to uncover genetic changes that contribute to tumor development. Infection of transgenic mice with Friend murine leukemia virus (F-MuLV) shortened the latency of morbidity to 103 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…The short variant is differed from long form by 39 base pairs, that reflects the loss of the exon 2 of Aml1 gene during rearrangement or in the process of alternative splicing. 1 It is known that various splice-variants/transcripts of fusion genes can be associated with different clinical features. For example, leukemic clone expressing Bcr-Abl p210 is more responsive to Gleevec therapy comparing with Bcr-Abl p190 positive cells.…”
Section: Number Of Cases Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…The short variant is differed from long form by 39 base pairs, that reflects the loss of the exon 2 of Aml1 gene during rearrangement or in the process of alternative splicing. 1 It is known that various splice-variants/transcripts of fusion genes can be associated with different clinical features. For example, leukemic clone expressing Bcr-Abl p210 is more responsive to Gleevec therapy comparing with Bcr-Abl p190 positive cells.…”
Section: Number Of Cases Diagnosismentioning
confidence: 99%
“…High-molecular-weight DNA was extracted from frozen spleen tumors and inverse PCR was performed as described (1). PCR products from the secondary PCR reaction were cloned into pAMP1-cloning vector (Gibco BRL).…”
Section: Number Of Cases Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that clonal growth of MuLV-infected cells results from insertional mutagenesis through integration in or around various growthrelated genes (15,16). A similar mechanism was recently proposed for ATL (17,18).…”
Section: Proviral Integration Sitesmentioning
confidence: 97%
“…A number of complementation studies have revealed that genes belonging to mitotic and antiapoptotic pathways are powerful cooperation partners in the clonal evolution of TAg‐associated tumors. Well‐studied examples are (proto‐)oncogenic receptors, such as Csfr1=c‐Fms, 15 signal transducers, such as Ras 15,16 or Src, 15 transcription factors, such as Fli1, 17 and apoptosis modulators, such as Bcl2. 18 Moreover, it has been shown that TAg acts as a chaperone, collaborating with cellular heat shock proteins ( Hsp ) 11 …”
Section: Introductionmentioning
confidence: 99%